The strong metric dimension of generalized Sierpiński graphs with pendant vertices - Estaji, Ehsan (Ars mathematica contemporanea, 2017)
Let ?$G$? be a connected graph of order ?$n$? having ?$ε(G)$? end-vertices. Given a positive integer ?$t$?, we denote by ?$S(G, t)$? the ?$t$?-th generalized Sierpiński graph of ?$G$?. In this note we show that if every internal vertex of ?$G$? is a cut vertex, then the strong metric dimension of ?$S(G, t)$? is given by ?$$\dim_s(S(G, t)) = \frac{ε(G) (n^t - 2n^{t-1} +1) - n + 1}{n-1}. $$?
Keywords: grafi; grafi Sierpińskega; krepka metrična dimenzija